Treatment of Complex Mandibular Body Fractures and Functional Reimplantation of the Maxillary Alveolar Fragment - Beatriz Sobrinho Sangalette; Rafaella Ferrari Pavoni; Thayna da Silva Emídio; Tiago Levatti; Marcos Capelari; Cláudio Maldonado Pastori; Gustavo Lopes Toledo (Case Reports in Surgery)
Introduction. This report aims at demonstrating the treatment of complex mandibular fracture functional reimplantation of the maxillary alveolar fragment (FRAF), denoting the possibility and feasibility of this reduction with an excellent prognosis. Case Report. Patient E.M.S, 25 years old, male, leucoderma, referred to the Emergency Room of our institute. He reported being a victim of physical aggression, occlusal alteration, limitation of mouth opening, sensibility loss in the mentalis region, right infraorbital, and denied visual alteration. On physical examination, during the inspection and palpation, the crackling was observed in the right mandibular region and apical displacement of the maxillary alveolar process, corresponding to elements 13, 14, and 15. Conclusion. The rigid fixation of the complex jaw fracture and alveolar maxilla process, through functional reduction, indicated satisfactory applicability, and favorable prognosis.